Factors influencing intention to comply with local sales tax in Malaysia - Bidin, Zainol; Mohd Shamsudin, Faridahwati; Shalihen, Mohd Salleh; Mohd Zainudin, Othman (Social Science Electronic Publishing, Inc, 2011)
Previous literatures indicate a number of variables that could possibly influence tax compliance behavior especially with respect to direct taxes.However, the variable behavioral intention was not widely considered when it is argued to be the main antecedent of behavioral compliance.Hence, the present study was conducted to identify the variables that could influence behavioral intention to comply with local sales tax, i.e. one of the many different types of indirect taxes.Toward this purpose, theory of planned behavior was used as the basis for the research.Three-hundred and thirty eight local sales tax agents in Malaysia participated in the research.Multiple regressions were employed to examine the relationship between attitude, subjective norm, and perceived behavioral control, on behavioral intention to comply with local sales tax.Results showed that attitude, primary and secondary subjective norms, and ethics are significantly and positively related to behavioral intention.All these independent variables were able to explain 64% variance in behavioral intention to comply with local sales tax.Implications and recommendations for policy makers are discussed.